Prototype of readout electronics for GAEA gamma spectrometer of Back-n facility at CSNS. (1st March 2022) - Xie, L.; Cao, P.; Yu, T.; Jiang, Z.; An, Q.; Li, J.; Li, C.; Wu, X.; Wang, Z.; Bai, H.; Bai, J.; Bao, J.; et al.
Abstract: The back-streaming neutrons (Back-n) facility at China Spallation Neutron Source (CSNS) provides an excellent white neutron source for accurate nuclear data measurements. At Back-n, the GAmma spectrometer with GErmanium Array (GAEA) in planning is designed to measure neutron-induced cross-sections, nuclear structure, and in-beam nuclear spectroscopy. As GAEA consists of various detectors, developing and maintaining the readout electronics for this spectrometer is challenging. A prototype of readout electronics based on the universal digital readout platform is proposed in this paper. The digitizer in the platform consists of a data processing carrier and a signal acquire mezzanine. Different mezzanines are designed to accommodate various detectors in GAEA. The carrier's firmware also has a universal part for data readout and a reconfigurable module for real-time data processing. In order to synchronize all digitizers, a time synchronization module is designed, based upon which a global synchronous network is constructed with PXIe chassis. Critical signals as the clock, trigger, and control can be synchronously distributed over this network with high precision, significantly simplifying the whole readout electronics. Several tests were carried out to evaluate the prototype. The measured FWHM of the 22 Na characteristic peak at 1274.5 keV is better than 0.15% for the HPGe detector. The measured time resolution of the readout electronics is 34.7 ps. Test results show that the performance of the readout electronics can meet GAEA requirements.